2010
DOI: 10.1177/0003122410388491
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Foundations of Tokenism

Abstract: Existing explanations of tokenism predict similar experiences for all numerically small, low-status groups. These explanations, however, cannot account for variation in the experiences of different low-status minority groups within the same setting. This article develops a theory of tokenism that explains such variation. Drawing on 117 interviews in the leveraged buyout industry (LBO) and a comparison of the differing experiences of female and African American male tokens in that setting, I argue that tokenism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(52 citation statements)
references
References 37 publications
3
32
0
4
Order By: Relevance
“…Consistent with scholarship that has found gender (dis)advantage to be context-specific (e.g., Turco, 2010;Ridgeway, 2011), I found that civilian female providers were generally more successful than male civilian providers, even though masculinity was more highly valued in this male-dominated context. There may be two reasons for this.…”
Section: Contributions To Our Understanding Of Influence By Low-powersupporting
confidence: 82%
“…Consistent with scholarship that has found gender (dis)advantage to be context-specific (e.g., Turco, 2010;Ridgeway, 2011), I found that civilian female providers were generally more successful than male civilian providers, even though masculinity was more highly valued in this male-dominated context. There may be two reasons for this.…”
Section: Contributions To Our Understanding Of Influence By Low-powersupporting
confidence: 82%
“…On the other hand, white female judges received a disproportionate number of assignments, as expected, but contrary to expectations in H3, female judges were 2.4% more likely to be assigned a case. Although we can only speculate, our findings potentially provide evidence for other research suggesting that (1) race stereotypes are activated before gender stereotypes (Ito and Urland 2003), which may explain their primacy in discretionary opinion assignment or (2) gender's effects are shaped by the courts'-specific cultural context (Turco 2010), which may be more sensitive to gender than race equity in discretionary assignment. Engaging these possibilities are tasks for future research.…”
supporting
confidence: 55%
“…Accordingly, many women avoid using the reduced-hours policies that are available to them out of concern for the career penalties that would result (Bailyn 1993(Bailyn [2006, Blair-Loy and Wharton 2002, Briscoe andKellogg 2011). Such concerns are well founded, as women who use reduced-hours policies experience slower wage growth (Glass 2004), fewer promotions (Kalleberg and Reskin 1995), lower quality work assignments (Stone and Hernandez 2013) and difficulty maintaining relationships with mentors (Turco 2010). Consequently, relatively low uptake of reduced-hours policies by the employees who stand to benefit the most from them has proven to be a "remarkably resilient problem" (Williams et al 2013, p. 209).…”
Section: )mentioning
confidence: 99%
“…4 Even a limited amount of remote working could meaningfully reduce the conflict between work and family demands for women, potentially improve their job performance, and-critically-be appealing enough to men as to result in gender-neutral usage patterns. The latter point is particularly important, insofar as the gendered nature of reduced-hours policy usage perpetuates the very stereotypes regarding commitment and competence that continue to hinder women professionally (Epstein et al 1999, Blair-Loy 2003, Ridgeway and Correll 2004, Turco 2010.…”
Section: )mentioning
confidence: 99%